Przyczyny braku kontroli astmy oskrzelowej na podstawie literatury = Reasons for lack of asthma control based on the literature - Katarzyna Dońka; Iwona Czerwińska Pawluk; Violetta Paździor; Walery Zukow (Kazimierz Wielki University, 2015)
Dońka Katarzyna, Czerwińska Pawluk Iwona, Paździor Violetta, Zukow Walery. Przyczyny braku kontroli astmy oskrzelowej na podstawie literatury = Reasons for lack of asthma control based on the literature. Journal of Education, Health and Sport. 2015;5(1):263-273. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.44380 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A263-273 https://pbn.nauka.gov.pl/works/688607 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2015. Revised 18.01.2015. Accepted: 21.01.2015.   PRZYCZYNY BRAKU KONTROLI ASTMY OSKRZELOWEJ NA PODSTAWIE LITERATURY Reasons for lack of asthma control based on the literature   Katarzyna Dońka Uniwersytet Medyczny w Lublinie, Katedra i Zakład Pielęgniarstwa Pediatrycznego   Iwona Czerwińska Pawluk Radomska Szkoła Wyższa, Wydział Nauk o Zdrowiu, Radom ul. 1905 roku Uniwersytecki Szpital Dziecięcy, Lublin. ul. Prof.. A. Gębali 6   Violetta Paździor Uniwersytet Medyczny w Lublinie, Katedra i Zakład Pielęgniarstwa Pediatrycznego   Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki       Streszczenie   Brak kontroli astmy oskrzelowej najczęściej spowodowany jest nieprzestrzeganiem przez pacjentów zaleceń lekarskich (noncompliance). Trudności w kontroli astmy zwiększają prawdopodobieństwo wystąpienia stanu astmatycznego. Pacjenci z astmą niekontrolowaną korzystają częściej z wizyt lekarskich, są częściej hospitalizowani i częściej trafiają na Szpitalny Oddział Ratunkowy. Rozwiązaniem tego problemu jest objęcie pacjentów programem szkoleniowym dotyczącym terapii astmy i możliwości kontroli choroby.   Słowa kluczowe: astma oskrzelowa, kontrola choroby, przyczyny braku kontroli astmy.   Abstract   Lack of control of asthma is most often caused by failure patients' medical recommendations (noncompliance). The difficulties in the control of asthma, increase the likelihood of status asthmaticus. Patients with uncontrolled asthma often use the visits, they are more often hospitalized and more likely to get on Hospital Emergency Ward. The solution to this problem is to extend patient training program on asthma therapy and the ability to control the disease.   Keywords: asthma, diabetes control, reasons for the lack of asthma control.